Squash : steps to success - Yarrow, Philip , 1968-; Harrison, Aidan , 1971- (Steps to success sports series, 2010)
"With 13 progressive instructional steps, you'll learn all aspects of the game of Squash. Detailed descriptions, illustrations, and photo sequences demonstrate essential on-the-court movement, volleys, serves, returns, and drop shots. Then practice and improve techniques with 93 drills, each featuring a personal scoring system to gauge and accelerate your progress"